The International Business Archives Handbook : Understanding and managing the historical records of business - Turton, Alison (London : Taylor and Francis, 2017)
"The International Business Archives Handbook provides up-to-date information and guidance on key issues relating to the understanding and management of the historical records of businesses.Key features include: Chapter contributions from a range of experts in their respective fields. Content covering business archive and business history initiatives around the world. Practical advice combined with thought-provoking discussion on issues hitherto little addressed. Useful quick-reference tables, global case study examples and further reading suggestions.The handbook is an invaluable guide for students, archive professionals and business historians alike. It is also an important reference tool for business professionals involved in information management more generally."--Provided by publisher.
part, 1 Business archives in context -- chapter 1 An introduction to business archives / Katey Logan -- chapter 2 The development of international business / Roy Edwards Kevin Tennent -- chapter 3 Changes in office technology / John Orbell -- part, 2 The nature of business records -- chapter 4 Understanding core business records / Michael Moss -- chapter 5 Understanding industry-specific business records / Lesley Richmond -- part, 3 Managing business archives -- chapter 6 Organisation and objectives / Jeannette Strickland -- chapter 7 Acquisition, appraisal, arrangement and description / Richard Wiltshire -- chapter 8 Preservation / Alison Turton -- chapter 9 Access / Alison Turton -- chapter 10 Managing digital business archives / William Kilbride James Mortlock Tina Staples -- chapter 11 Managing risk / Sara Kinsey -- part, 4 Using business archives -- chapter 12 Advocacy, outreach and the corporate archivist / Paul C. Lasewicz -- chapter 13 The business history discipline / Leslie Hannah.
Keywords: Business enterprises; Business records -- Management; Business History; Library & Information Science